2020
DOI: 10.1177/0734242x20947158
|View full text |Cite
|
Sign up to set email alerts
|

The influencing factors of Harbin (China) residents’ satisfaction with municipal solid waste treatment

Abstract: China is experiencing an enormous increase in municipal household solid waste (MHSW) generation and is facing multiple problems associated with the treatment of MHSW. This paper analyses factors affecting residents’ satisfaction with MHSW treatment performance. Six factors were identified by the Delphi method: (a) pick-up frequency by waste collection vehicles, (b) fund supply situation, (c) charging standard for waste treatment, (d) waste bin arrangement, (e) laws and regulations, (f) publicity and education.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Over time, propaganda and education on the mass media such as DRT, Da Nang newspaper, ..., or having meetings of residential blocks for reference and discussion in activities of waste sorting have made a significant contribution to the environmental quality. This clearly shows the responsibility of the city in social management in general and environmental management in particular [17]. Thus, this has created more trust, satisfaction, and support of the people with the movements proposed by the city.…”
Section: Test the Model By Semmentioning
confidence: 84%
See 3 more Smart Citations
“…Over time, propaganda and education on the mass media such as DRT, Da Nang newspaper, ..., or having meetings of residential blocks for reference and discussion in activities of waste sorting have made a significant contribution to the environmental quality. This clearly shows the responsibility of the city in social management in general and environmental management in particular [17]. Thus, this has created more trust, satisfaction, and support of the people with the movements proposed by the city.…”
Section: Test the Model By Semmentioning
confidence: 84%
“…People"s expectations are a type of pre-performed belief about a good or service [15]. The quality of waste classification service at source refers to the frequency of collection, the time of garbage collection, and the arrangement of the garbage bins [16], [17]. The quality of waste treatment services in the community has to meet people"s expectations [8]- [10].…”
Section: Analytical Framework and Research Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…With the help of this model, the treatment methods and their capacity can be determined, indicating possible optimal design solutions and recommendations. Chu et al (2021) have identified the influencing factors of Harbin (China) residents' satisfaction with municipal solid waste treatment. Based on their research, they have advocated that establishing a reasonable waste transport and education of waste management are key to improving residents' satisfaction with the municipal household solid waste treatment performance.…”
Section: Literature Surveymentioning
confidence: 99%